Efficacy, safety and tolerability of three regimens of artemisinin combination therapy in the management of Plasmodium falciparum malaria: a comparative study - Halkai, Komal Mallinath; Patil, Bapugouda Sahebagouda (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The WHO now recommends the use of artemisinin-based combination therapies for the first-line treatment of Plasmodium falciparum malaria to reduce the drug resistance. Hence, this study was designed to compare the efficacy, safety and tolerability of three regimens of artemisinin combination therapies in malaria diagnosed patients of Kamineni Institute of Medical Sciences Hospital, Narketpally. Methods: Total of 104 subjects had been allocated to 3 different artemisinin-based combinations regimens in a period of 2 years during December 2013 - November 2015. Out of 104 subjects, 34 received artemisinin-sulphadoxine pyrimethamine regimen, 33 subjects received artemisinin-lumefantrine regimen, and 37 subjects received artemisinin-doxycycline regimen. All the three regimens were studied for their efficacy, safety and tolerability. Results: The mean number of febrile days in artesunate-sulfadoxine pyrimethamine group (3.43±0.92) and artesunate-doxycycline group (3.51± 0.74) were comparatively less than artemether-lumefantrine group (4.33±0.77) which is statistically significant. The mean Hb%, RBC count, WBC count was not significantly different on day 7 in comparison to day 1 in all the three regimens of treatment groups. 14 subjects among the 104 had mild thrombocytopenia which was significantly improved on day 7 in all the three regimens of treatment groups. Conclusions: Artesunate-sulfadoxine-pyrimethamine and artesunate-doxycycline regimens showed better efficacy, safety and tolerability than artemether-lumefantrine regimen.